Examining the effect of emotional intelligence on socio-demographic variable and job stress among retail employees - Abhishek Shukla; Rajeev Srivastava (Cogent Business & Management, 2016)
The purpose of the present study is to explore the relationship between emotional intelligence, socio-demographic variable, job stressors and examine the moderating effect of emotional intelligence on the relationship between socio-demographic variable and job stress. The data were analyzed on the sample of 564 retail employees using descriptive statistics, Pearson correlations, and hierarchical multiple regression. The result shows that there is a socio-demographic difference with respect to trait emotional intelligence (EI) and job stress. The proposed model is a good predictor of job stress. Trait EI is more significant influencing factor for job stress than gender, age, marital status, education, annual income and work experience. Specifically, the present study suggests that intervention aimed at reducing job stress if it includes enhancement of employees with high emotional intelligence rather than just decreasing external stressors.
Keywords: 650